Scope and Limits of a Prosodic Map [Alcances y Límites de Un Mapa Prosódico] - Roman-Montes de Oca, D (Pontificia Universidad Catolica de Chile, 2020)
This paper presents the first "Prosodic Map of Chile", a long-term project aimed at documenting and describing (both phonetically and phonologically) the suprasegmental features of Chilean Spanish. In order to better appreciate the map s reach, a review of currently implemented similar prosodic maps is provided, including AMPER, ATLES and some others. This review considers what particular parameters are studied in each map, closely inspecting what are the foundations, directions and the overall reach of each one of them. The closing section provides a consideration of some freely available software tools designed to build maps, particularly OpenStreetMap, focusing on its potential for future international collaborative efforts. © 2020 Pontificia Universidad Catolica de Chile. All rights reserved.